Pengukuran Nilai pH Dan Kadar BOD (Biological Oxygen Demand) di Telaga Belahan Rejo Sebagai Pemantauan Kualitas Air Di Kabupaten Gresik - Sa'adah, Nafiatus; Zummah, Atiqoh; Teguh Pribadi, Eko; Safarina, Nourma (Chemistry Department, Universitas Islam Indonesia, 2024)
Belahan Rejo Lake is one of the water bodies in Gresik Regency. Belahan Rejo lake water is used by the surrounding community for daily purposes such as irrigation of rice fields, plantations, fisheries, domestic, and so on. Activities carried out by the community around Belahan Rejo lake can affect water quality and can even cause water pollution. The purpose of this study is to determine the quality of Belahan Rejo lake water in terms of pH and BOD (Biological Oxygen Demand) parameters. Analysis of pH values is carried out based on the SNI 6989.11: 2019 method using a pH meter tool while analysis of BOD levels is carried out based on the SNI 6989.72: 2009 method by looking at the value of dissolved oxygen using a DO meter tool. The results of the analysis show that Telaga Water in Belahan Rejo Hamlet, Gresik Regency is in accordance with quality standards with a pH value of 6.5 and Biological Oxygen Demand (BOD) levels of 5.1 mg/L.